More Women Must Lead in Global Health: A Focus on Strategies to Empower Women Leaders and Advance Gender Equality - Amie Batson; Geeta Rao Gupta; Michele Barry (Ubiquity Press, 2021)
Despite comprising 70% of the health workforce, women fill only 25% of senior and 5% of top health organization positions. Greater diversity in global health leadership, particularly greater representation of women, is essential to ensure diverse perspectives and ideas inform policies and priorities. Interviews and literature reviews surfaced many of the key challenges that women in global health face at individual, organizational and societal levels. Initiatives working to advance women's leadership are encouraged to consider 5 key priorities that address these challenges.